Discrepancy between Knowledge and Practice Regarding Antimicrobial Resistance among Retail Pharmacists in Sana’a City, Yemen - Ibrahim H. Al-Subol; Amina H. Al-Moliky; Manar T. Nassar; Amani A. Al-Bakali; Farah A. Al-Mashreqi; Rawan J. Alwajeh; Khairya S. Al-Jabri; Roa'a A. Shafi; Kholoud N. Morad; Doaa A. Alezzi (University of Science and Technology, Sana’a, Yemen, 2026)
Background: Antimicrobial resistance (AMR) is a growing global health threat. While improving knowledge is a key part of antimicrobial stewardship (AMS), a significant gap often exists between what healthcare providers know and what they actually practice. assess retail pharmacists’ knowledge, awareness, and dispensing practices regarding AMR and its contributing factors in Sana’a City, Yemen. Methods: A cross-sectional survey was conducted among 300 conveniently sampled retail pharmacists from nine districts in Sana’a City, Yemen, between October 2023 and January 2024. Data were collected using a structured, self-administered questionnaire assessing pharmacists’ demographic and professional characteristics, knowledge of AMR, awareness of its factors contributing, and antibiotic-dispensing practices. Knowledge and awareness items were scored on a 3-point Likert scale, while dispensing practices were assessed using a 5-point Likert scale. Scores were converted to percentage values and categorized as good or poor using a 75% cutoff. Associations of pharmacists’ characteristics with their knowledge, awareness, and practices were examined using chi-square or Fisher’s exact tests, with statistical significance set at P <0.05. Results: Most pharmacists demonstrated good knowledge of AMR, where 83.7% correctly defined AMR, 88% recognized it as a major global health problem, and 88.7% identified it as a direct threat to human health. Microbial mutations were recognized as a key driver of AMR by 84.3%, while only 51% acknowledged genetic transmission, and fewer recognized healthcare-associated spread (42.3%) or hospital-acquired resistant infections (45.7%). Awareness of contributing factors was high, including inappropriate antibiotic use (85.7%), treatment interruption (93.3%), suboptimal dosing (77.7%), use of broad-spectrum antibiotics (61.3%), antibiotic use in livestock (86.3%), and environmental contamination (83.3%). Despite high levels of good knowledge (86%) and awareness (86.7%), poor antibiotic-dispensing practices were common (86.0%), with 35.7% reporting dispensing antibiotics without prescription. Pharmacists with a bachelor’s degree had higher odds of good knowledge and awareness than those holding a diploma degree (OR = 2.1, 95% CI: 1.06–4.03; P = 0.034 and OR = 2.0, 95% CI: 1.03–4.05; P = 0.040, respectively). Conclusion: Retail pharmacists in Sana’a exhibit a notable level of knowledge and awareness of AMR and its contributing factors, but this level does not translate into good antibiotic-dispensing practices. This discrepancy underscores the pressing necessity for a comprehensive strategy that goes beyond existing AMS by implementing mandatory training, educational workshops, and strict enforcement of dispensing regulations. Further research into the social and professional drivers of these practices is essential to develop more effective, targeted interventions.